Boron-Wittig olefination with gem-bis(boryl)alkanes. (15th December 2020) - Cuenca, Ana B.; Fernández, Elena
Abstract : Boron-Wittig reaction as the condensation of lithium α-bis(boryl)carbanions with carbonyl derivatives on route to substituted borylalkenes. Abstract : The condensation of easy manageable lithium α-bis(boryl)carbanions with carbonyl derivatives, the so-called boron-Wittig reaction, allows for the straightforward and often stereoselective formation of synthetically highly versatile metalloid-substituted alkenes, which are key building blocks on route to all-carbon substituted olefins. In this Tutorial review the concept behind this olefination reaction and its application to ketones, aldehydes and other carbonyl derivatives, such amides, ester and carboxylic acids, are presented in a systematic manner. A special emphasis has been placed on parameters controlling the stereochemical outcome of these transformations. To illustrate the great synthetic potential of this new methodological tool, a section is also included covering a selection of applications of the boron-Wittig reaction to target compounds via subsequent C–C bond-forming process.